2008
DOI: 10.1002/jcu.20452
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic wall motion of healthy and hypertensive subjects: Evaluation of tissue Doppler velocity imaging

Abstract: This study provides evidence that abdominal aortic wall motion measurement with TDI could demonstrate qualitative and quantitative wall motion features differentiating hypertensive from healthy adults. Wall motion velocity and PWTT could reflect abdominal aortic compliance changes related to age, sex, and blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Both may influence the dynamic behaviour of the aortic root and may be a confounder in the presented results. Studies have showed that the aortic stiffness is increased in patients with hypertension [33, 34]. Therefore, It could be that the dynamic changes in subjects with lower blood pressures are even more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Both may influence the dynamic behaviour of the aortic root and may be a confounder in the presented results. Studies have showed that the aortic stiffness is increased in patients with hypertension [33, 34]. Therefore, It could be that the dynamic changes in subjects with lower blood pressures are even more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic early diastolic pw‐TDI velocity (Ea‐aorta) is higher in the control group (Group 1) compared to the patients with LVDDF (Groups 2 and 3). AS 17,18 and Ea‐aorta 32–34 being the main determinant of increased aortic stiffness have been shown in the studies that have been done up to now. So, according to the results of our study, it could be clearly said that increased aortic stiffness and LVDDF togetherness are present in the cases without CAD.…”
Section: Discussionmentioning
confidence: 79%
“…SRI is widely used for the evaluation of myocardial motion, and its use for the assessment of large vessel wall elasticity has been shown to be feasible and accurate . However, because of its deep location, the abdominal aorta IMT cannot be measured accurately using high‐frequency ultrasound transducers.…”
Section: Discussionmentioning
confidence: 99%